The force - Winslow, Don, 1953- (New York : William Morrow, an imprint of HarperCollins Publishers, 2017)
Danny Malone, highly decorated NYPD detective sergeant, is a dirty cop. He has stolen millions of dollars in drugs and cash in the wake of the biggest heroin bust in New York City's history. Now Malone is caught in a trap and being squeezed by the Feds, and he must walk the thin line between betraying his brothers and partners, the Job, his family, and the woman he loves.
Keywords: Police -- New York (State) -- New York -- Fiction; Police corruption -- New York (State) -- New York -- Fiction; Thrillers (Fiction); Detective and mystery fiction